2015
DOI: 10.1142/s0217732315500418
|View full text |Cite
|
Sign up to set email alerts
|

An asymptotic method for selection of inflationary modes

Abstract: We present some features of early universe cosmology in terms of Hankel functions index ( ν ). Actually, the recent data from observational cosmology indicate that our universe was nearly de Sitter space-time in the early times which results in an approximate scale-invariant spectrum. This imposes some constrains on index ν [1]. These constrains stimulate us to use general solution of inflaton field equation for ν = 3 2 . To obtain the general solution for the inflationary background, we use asymptotic expansi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Bunch-Davies) limit. In fact, taking into account the resent observational constraint together with the result obtained in [36] motivates us to use quasi-de Sitter curved space-time and excited mode functions. We have seen that slight deviation of the Bunch-Davies mode leads to corrections in the primordial gravitational potential spectra and in the large angular scales CMB anisotropy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bunch-Davies) limit. In fact, taking into account the resent observational constraint together with the result obtained in [36] motivates us to use quasi-de Sitter curved space-time and excited mode functions. We have seen that slight deviation of the Bunch-Davies mode leads to corrections in the primordial gravitational potential spectra and in the large angular scales CMB anisotropy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as a result of using this excited initial state, it has been shown that we can have particle creation [35]. They have also been used to calculate the scale-dependency of the primordial power spectrum [36]. In this work, it is expected that employing an initial excited de Sitter mode for calculating the primordial perturbed gravitational potential leads to the breaking of angular-scale symmetry in the CMBA power spectrum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If we suppose that cosmic inflation is described by dS space-time, there exists a concrete set of vacuum states invariant under the dS group. However, as we know, an inflationary universe is described by quasi-dS space-time, that may be exact dS in the first approximation [37]. Recently, as an approximate solution for quasi-dS space-time, we have added a perturbative second order term 1 2 ( ±i kτ ) 2 to the dS mode function (18) in [38] and have derived non-linear trans-Planckian corrections in the spectra.…”
Section: Asymptotic-ds Vacuum For Quasi-ds Inflationmentioning
confidence: 99%
“…quasi-de Sitter vacuum. Therefore, we have introduced the asymptotic-de Sitter modes for the first time in [16][17][18][19], as the main vacuum modes during inflation to study the subject of the particle creation. Compared to pure de Sitter inflation, particles created during quasi-de Sitter inflation have effective mass and non-minimal coupling with gravity that appears to be due to the change in the curvature of the space-time from de Sitter one [20,21].…”
mentioning
confidence: 99%